Il gesto rivoluzionario dell’infanzia. Avanguardia teatrale e liberazione delle facoltà estetiche nel teatro per bambini di Asja Lacis - Vitali, Rolando (Aesthetica Preprint, 2025)
The paper provides a philosophical analysis of the pedagogical theatre experiment carried out by Asja Lacis in the city of Orel in Soviet Russia in 1918. Lacis’s experimentation is first traced back to the modern German tradition of theatre as a “moral institution” in Friedrich Schiller and Richard Wagner. In light of this tradition, Lacis’s work is then contextualized within the avant-garde movement, showing how it develops in an original way the idea of “leading art back into social life” (Peter Bürger), by overcoming the notion of aesthetic autonomy and radicalizing the pragmatic dimension of the aesthetic field.